Political Economy Study of Fishermen in Kupang City - Lasarus Jehamat; Yosep Emanuel Jelahut; Christine E. Meka; Balkis Soraya Tanof; Aris Lambe; Felisianus Efrem Jelahut (Jurnal Pluralis, 2024)
The focus of this research is to look at the dynamics and patterns of fishermen's struggle to survive and confirm their identity as fishermen in Kupang. The purpose of this study is to explain the study of political economy in Kupang City, East Nusa Tenggara. The theory used in this study is the theory of income. The method used in this research is qualitative with data collection techniques in the form of in-depth interviews, observation and focus group discussions. The results of the study show that the covid-19 pandemic has an impact on the income of fishermen in Kupang city, both for ship owners, captains/captains, crew members (ABK) and catch collectors/gatherers. The impact is in the form of a decrease in the income earned by fishermen. The decrease in revenue was due to constraints in marketing the main catch, namely bubble fish which became an export commodity abroad. The decrease in income was also caused by the increase in the number of operational costs in fishing activities such as the cost of vitamins, medicines, masks and medical tests if needed. In trading activities, traders are people or institutions that trade products or goods to consumers, either directly or indirectly.